Increased levels of mitochondrial import factor Mia40 prevent the aggregation of polyQ proteins in the cytosol. (30th June 2021) - Schlagowski, Anna M; Knöringer, Katharina; Morlot, Sandrine; Sánchez Vicente, Ana; Flohr, Tamara; Krämer, Lena; Boos, Felix; Khalid, Nabeel; Ahmed, Sheraz; Schramm, Jana; Murschall, Lena M; Haberkant, Per; et al.
Abstract: The formation of protein aggregates is a hallmark of neurodegenerative diseases. Observations on patient samples and model systems demonstrated links between aggregate formation and declining mitochondrial functionality, but causalities remain unclear. We used Saccharomyces cerevisiae to analyze how mitochondrial processes regulate the behavior of aggregation‐prone polyQ protein derived from human huntingtin. Expression of Q97‐GFP rapidly led to insoluble cytosolic aggregates and cell death. Although aggregation impaired mitochondrial respiration only slightly, it considerably interfered with the import of mitochondrial precursor proteins. Mutants in the import component Mia40 were hypersensitive to Q97‐GFP, whereas Mia40 overexpression strongly suppressed the formation of toxic Q97‐GFP aggregates both in yeast and in human cells. Based on these observations, we propose that the post‐translational import of mitochondrial precursor proteins into mitochondria competes with aggregation‐prone cytosolic proteins for chaperones and proteasome capacity. Mia40 regulates this competition as it has a rate‐limiting role in mitochondrial protein import. Therefore, Mia40 is a dynamic regulator in mitochondrial biogenesis that can be exploited to stabilize cytosolic proteostasis. SYNOPSIS: The accumulation of mitochondrial precursor proteins in the cytosol induces the formation of protein aggregates. Overexpression of mitochondrial import factor Mia40 improves mitochondrial protein import and increases resistance against proteotoxic insults in Saccharomyces cerevisiae . S. cerevisiae mitochondrial import mutants are hypersensitive to cytosolic polyQ proteins. Overexpression of Mia40 prevents the formation of polyQ aggregates in yeast and human cells. Mia40 levels affect the solubility of the cytosolic prion protein Rnq1. Increasing mitochondrial import augments robustness of cytosolic proteostasis. Abstract : Mia40‐mediated import of mitochondrial precursor proteins increases resistance against proteotoxic insults and stabilizes cytosolic proteostasis in Saccharomyces cerevisiae .